Beat it, Rufus - Van Sciver, Noah (Fantagraphics Books Inc., 2025)
"...a hysterical character comedy about an aging rock-god-in-his-own-mind forced to face the music. Rufus Baxter is an aging, professionally unemployed loser, desperately -- delusionally -- hanging on to his 1980s hair metal fantasies of headlining arenas, despite so much evidence to the contrary (like audience members ducking when he tosses promo t-shirts at an open-mic night). The rest of his bandmates in Funky Cool died decades ago in a horrible plane crash on the cusp of their first big break. When he gets kicked out of the Denver storage unit he's been illegally sleeping in, his only prospect is a last-second wedding gig the very next day - in Wyoming. A hop in his car, and possibly a peyote button or two, sends Baxter on a psychedelic and existential road trip through his past, and forces him to confront every bad decision he's made along the way."--Publisher.